Asuhan Kebidanan Ny “Y” G2P1A0 Hamil 17 Minggu dengan Hipermesis Gravidarum 2024 - Rosmiarti, Rosmiarti; Berlianti, Matsna (Ners Akademika, 2025)
Purpose: This case study aims to describe and analyze midwifery care in a case of hyperemesis gravidarum, a pregnancy complication that can significantly impact maternal and fetal health. Method: The subjects of the study were taken by purposive sampling, namely 67 lecturers from midwifery institutions. Data were analyzed using descriptive and inferential statistics, namely the Chi Square test, Wilcoxon test and Mann Whitney test, Logistic Regression tesThe research subject was Mrs. Y, G2P1A0, with a gestational age of 17 weeks and 6 days, experiencing excessive nausea and vomiting. Data collection methods included interviews, physical examinations, and analysis of medical records. Results: The results showed that Mrs. Y experienced a weight gain of 14 kg, normal blood pressure, and a MUAC of 39 cm. The management provided included education, pharmacological therapy, dietary modifications, and psychosocial support. Although some 10T examination data were incomplete, the care provided was in accordance with hyperemesis gravidarum management standards. Conclusion: This study concludes the importance of a holistic and multidisciplinary approach in managing hyperemesis gravidarum to optimize maternal and fetal health. Limitations: Incomplete documentation of some 10T examination data limited the comprehensiveness of case analysis. Contribution: This study contributes to strengthening evidence-based midwifery care practices for hyperemesis gravidarum through integrated clinical, educational, and psychosocial interventions.